Experimental and numerical study of a diffuser augmented wind turbine - DAWT - Maia, Lino André Bala (2015)
The effect of concentrator-diffuser (C-D) of a shrouded wind turbine was studied. The main objective involved assessing the increment that this device induces in productivity of small wind turbines. Also the aerodynamic performance of two scaled blade models were studied in terms of drag and lift forces as a function of angle of attack for Re of 15714 and 37143. Wind turbine power performance was evaluated in terms of power coefficient values. Laboratory measurements showed that improvements were obtained on the electrical power values, resulting in an average increase of 90% in the corresponding power coefficient values. A more pronounced enhancement is described at lower wind speed values. CFD calculations were performed at flow values of 6 and 14 m/s to the C-D device. CFD calculations performed an evaluation of velocity experienced in the action rotor zone, which provided maximum increases of 81 % and 86 %, respectively. Numerical simulations and experimental measurements were performed also to the blades, where the results obtained were similar, providing a difference of 25 % for drag forces.